2020
DOI: 10.3390/nu12102925
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Oral Administration of Heat-killed Lactobacillus brevis KB290 in Combination with Retinoic Acid Provides Protection against Influenza Virus Infection in Mice

Abstract: Influenza virus type A (IAV) is a seasonal acute respiratory disease virus with severe symptoms, and an effective preventive measure is required. Despite many reports describing the potentially protective effects of lactic acid bacteria, few studies have investigated the effects of nutritional supplement combinations. This study reports the effect of the combined intake of heat-killed Lactobacillus brevis KB290 (KB290) and vitamin A (VA) on mice challenged with a sublethal dose of IAV. For 2 weeks, five groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Furthermore, the combination of beneficial probiotics and nutrients can be helpful for protection against respiratory virus infections [53 & ]. In a recent animal study, oral administration of heat-killed Lactobacillus brevis before influenza infection showed a significant reduction of viral titers in the lungs when combined with retinoic acid [53 ], which suggests that combination of the beneficial microbiome and nutrients can synergistically help to protect the respiratory function. Therefore, the combination of probiotics and nutrients can be applied in COVID-19 infections to decrease its severity, although further studies in patients with COVID-19 infection are needed to confirm the results.…”
Section: Potential Strategies To Decrease the Disease Burden Caused B...mentioning
confidence: 99%
“…Furthermore, the combination of beneficial probiotics and nutrients can be helpful for protection against respiratory virus infections [53 & ]. In a recent animal study, oral administration of heat-killed Lactobacillus brevis before influenza infection showed a significant reduction of viral titers in the lungs when combined with retinoic acid [53 ], which suggests that combination of the beneficial microbiome and nutrients can synergistically help to protect the respiratory function. Therefore, the combination of probiotics and nutrients can be applied in COVID-19 infections to decrease its severity, although further studies in patients with COVID-19 infection are needed to confirm the results.…”
Section: Potential Strategies To Decrease the Disease Burden Caused B...mentioning
confidence: 99%
“…The exclusion criteria were as follows: (1) those with a history of serious illness (liver/kidney/heart disease, organ damage, diabetes, food allergy disease, digestive disease, etc. ); (2) those who regularly consumed lactic acid bacteria-fortified foods or vegetable juices (more than three times a week); (3) smokers; (4) those with a history of exposure to asbestos; (5) those with severe pollinosis; (6) pregnant and/or lactating women, including those who were planning a pregnancy during the study; (7) alcoholics; (8) those who routinely took pharmaceuticals, foods for specified health use, foods with functional claims, and other health foods; (9) those who were allergic to the experimental beverages; (10) those who could not take the experimental beverages as directed; (11) participants of other clinical studies; (12) those who suffered from influenza between 1 September 2019, and the date of obtaining written informed consent; (13) health workers.…”
Section: Subjectsmentioning
confidence: 99%
“…Our previous in vivo study demonstrated that the administration of heat-killed Levilactobacillus brevis KB290 (KB290) or retinoic acid, a metabolite of VA, suppressed weight loss and viral titer elevations in mice challenged with IAV [ 12 ]. In addition, the administration of KB290 in combination with retinoic acid significantly suppressed weight loss rather than KB290 or retinoic acid alone [ 12 ]. These findings suggest that this combination could be an effective prophylaxis for daily use.…”
Section: Introductionmentioning
confidence: 99%